Comparison of two next-generation sequencing-based approaches for liquid biopsy analysis in patients with non-small cell lung cancer: a multicentre study. Issue 3 (14th June 2022) - Bessi, Silvia; Pepe, Francesco; Russo, Gianluca; Pisapia, Pasquale; Ottaviantonio, Marco; Biancalani, Francesca; Iaccarino, Antonino; Russo, Maria; Biancalani, Mauro; Troncone, Giancarlo; Malapelle, Umberto
Abstract : In the era of personalised medicine, testing for an increasing number of predictive biomarkers is becoming a priority. However, tissue biopsies from these patients are oftentimes insufficient for conventional approaches, a common issue that deprives them of the clinical benefits of biomarker-directed treatments. To tackle this problem, many clinical laboratories are resorting to circulating tumour DNA (ctDNA), which is becoming increasingly appreciated as a valuable source for biomarker testing. In this context, next-generation sequencing (NGS) has become essential. Indeed, different NGS systems are able to detect several clinically relevant low-frequency hot-spot mutations simultaneously in a single run. However, their reproducibility in the analysis of ctDNA has not yet been investigated. The purpose of this study was to evaluate the reproducibility of using Illumina MiSeq and Thermo Fisher Ion S5 Plus platforms to assess pathogenic alterations in non-small cell lung cancer (NSCLC) liquid biopsy specimens. Using the in vitro diagnostic (IVD) NGS panel Myriapod NGS Cancer panel DNA (Diatech Pharmacogenetics) on MiSeq platform (Illumina), we reanalysed ctDNA extracted from a retrospective series of n=40 patients with advanced NSCLC previously tested with a custom NGS panel (SiRe) on Thermo Fisher Ion S5 Plus system. Overall, 13 out of 40 (32.5%) ctDNA samples displayed pathogenic alterations in at least two genes, namely, EGFR and KRAS . A concordance rate of 100% was identified between the two methodologies in terms of sample mutational status and total number of detected variables. All NGS platforms featured a high degree of concordance.